Transcriptomic, Biochemical, and Morphological Study Reveals the Mechanism of Inhibition of Pseudopestalotiopsis camelliae-sinensis by Phenazine-1-Carboxylic Acid - Yin, Qiaoxiu; Yang, Rui; Ren, Yafeng; Yang, Zhiying; Li, Tao; Huang, Honglin; Tang, Qin; Li, Dongxue; Jiang, Shilong; Wu, Xian; Wang, Delu; Chen, Zhuo (Frontiers in Microbiology, 2021)
Gray blight disease is one of the most destructive diseases of tea plants, and occurs widely in the tea-growing areas of the world. It is caused by several fungal phytopathogens, of which Pseudopestalotiopsis camelliae-sinensis is the main pathogen in China. The environmentally friendly antimicrobial, phenazine-1-carboxylic acid (PCA), a metabolite of the natural soil-borne bacteria Pseudomonas spp., can inhibit a range of fungal crop diseases. In this study, we determined that PCA was active against Ps. camelliae-sinensis in vitro. We studied the mode of action, using a microscopic investigation of the effects of PCA on hyphal morphology, as well as identification of the fungal genes whose expression were affected by PCA, using transcriptomics. The results of scanning and transmission electron microscopy indicated that PCA caused developmental deformity of mycelia, organelle damage, and it significantly decreased the accumulation of exopolysaccharides on the hyphal surface. The transcriptome revealed that 1,705 and 1,683 differentially expressed genes of Ps. camelliae-sinensis treated with PCA were up-regulated or down-regulated, respectively, with genes associated with ribosome biogenesis, oxidative phosphorylation and encoding various proteins of N-glycan biosynthesis being significantly up-regulated. Up-regulation of nine genes related to N-glycan biosynthesis of Ps. camelliae-sinensis in response to PCA treatment was confirmed by quantitative real-time PCR. Our results indicated that exposure to PCA resulted in expression changes in oxidoreductase genes, accumulation of reactive oxygen species, and decreased activity of catalase but not superoxide dismutase, with concomitant damage to the fungal cell membrane and cell wall.